Chitosan from Marine Crustaceans: Production, Characterization and Applications - Dima, Jimena Bernadette (2017)
Chitosan is a very useful marine polysaccharide that forms structural components in the exoskeleton of crustaceans. In this chapter, the production of chitosan (CH) and chitosan reticulated micro/nanoparticles (CHM) is described. Three case studies corresponding to different effective applications of chitosan are discussed: (i) the performance of CH to destabilize oil/water emulsion waste for water clarification. It was observed that as long as colloidal charge was maintained around zero, turbidity also showed low values and water clarification was achieved. However, when the applied doses were higher than the optimum, colloidal charge and turbidity both increased, showing emulsion restabilization. Emulsions treated with the optimum chitosan doses were clarified in very short periods; (ii) CH and CHM were used as effective antibacterial agents against three different pathogenic microorganisms that are problematic for aquaculture: Vibrio alginolyticus and parahaemolyticus, and Lactococcus garvieae and theminimum bactericidal concentrations were determined; and (iii) the removal ofhexavalent chromium and the comparative performance of CH versus CHM. Resultsshowed that at pH < 2, the adsorption capacity of CHM was higher because CH isunstable. Additionally, Cr(VI) was adsorbed on CH without further reduction; incontrast, Cr(VI) adsorbed on CHM was reduced to nontoxic Cr(III).